DISTRIBUTION LEGALITY OF ARAK AS A BALI TRADITIONAL DRINK - I Wayan D. Gotama; I Dewa Gede Pradnya Yustiawan (Transpublika Publisher, 2022)
This study aims to understand and determine the distribution arrangements for arak as a traditional Balinese drink. The research method uses a normative legal research type, the type of approach uses a statutory approach and a case approach. The legal materials used are sourced from primary legal materials in the form of related legislation, while other sources are from literature, journals and internet media. The technique of collecting legal materials uses document study techniques and is processed in a qualitative descriptive way. The findings of the research, specifically the regulation of the distribution of arak as a traditional Balinese drink, are regulated in the Governor of Bali Province Regulation Number 1 of 2020 concerning the Governance of Balinese Fermentation and Distillation Drinks as a form of governance for the distribution of Balinese arak. The legality of distribution of arak as a traditional Balinese drink is carried out by producers through distributors, then carried out by sub-distributors and distributed to direct sellers.